IMPOLITENESS STRATEGY IN CYBERBULLYING COMMENTS FOUND ON THE SOCIAL MEDIA - Alda, Alda; Burhamzah, Muftihaturrahmah; Nur, Riola Haya (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to determine the forms of cyberbullying on social media and also determine the forms of disrespectful strategies carried out by social media users through social media reactions. This study used a descriptive qualitative method. Data is taken from online comments provided by social media users on Instagram, YouTube and TikTok. The data source was taken from the social media accounts of Kylie Jenner and Kim Kardashian. The results of this thesis prove that of the 34 extracts found from the two celebrity accounts, only 5 forms of cyberbullying were found from the two celebrity accounts, namely flaming consisting of 22 extracts, harassment 3 extracts, denigration 5 extracts, outing and trickery 2 extract, and exclusion. from 2extracts, no cyberstalking and impersonation were found from Kylie Jenner's account and Kim Kardashian's account. The next aim is the forms of incivility strategies used in cyberbullying comments. However, only 4 forms of impoliteness were found, namely 9 forms of positive impoliteness, 12 forms of negative impoliteness, 7 bald on record impoliteness, and finally 3 forms of sarcasm or mock impoliteness. We did not find polite restraint because polite restraint is not used at all in cyberbullying on social media. This results from cyberbullying's inappropriate goal of hurting, offending, and abusing people's feelings.